Russian church in the digital era mediatization of orthodoxy - Stähle, Hanna 1964- (London New York Routledge Taylor & Francis Group, 2022)
"The Russian Orthodox Church, the largest and most powerful religious institution in Russia, has become one of the central pillars of Vladimir Putin's authoritarianism. While church attendance remains low, the religiously inspired rhetoric of traditionalism has come to dominate the mainstream political and media discourse. Has Russia abandoned its atheist past and embraced Orthodox Christianity as its new moral guide? The reality is more complex and contradictory. Digital sources provide evidence of rising domestic criticism of the Russian Orthodox Church and its leadership. This book offers a nuanced understanding of contemporary Russian Orthodoxy and its changing role in the digital era. Topics covered within this book include: Mediatization theory Church reforms under Patriarch Kirill Church-state relations since 2009 Russian Orthodox Church's media policy Anticlericalism vs. Church criticism Religious, secular and atheist critiques of the Church in digital media Using contemporary case studies such as Pussy Riot punk prayer this book is a gripping read for those with an interest in media studies, digital criticism of religion, religion in the media, the role of religion in society, and the Russian Orthodox Church"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ -- History -- 21st century; Digital Media -- Religious aspects -- Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ; Mass Media -- Religious aspects -- Russkai︠a︡ pravoslavnai︠a︡ t︠s︡erkovʹ; Church and state -- Russia (Federation); Russia (Federation) -- Church history -- 21st century